BERLAKU ADIL DALAM KEMEWAHAN: PEMBACAAN ATAS AM 6:1-7 - Kartono . (SOLA GRATIA: Jurnal Teologi Biblika dan Praktika)
Abstract:  In the Book of Amos, the picture of social life is so factual. Unfortunately, this situation is dominated by a problematic situation where people are being oppressed by the authorities, whoever they are. But what needs to be looked at is whether social justice was possible at that time? The answer is perhaps as championed by the prophets, including the Prophet Amos. So, what does fairness mean? The story of the Prophet Amos, who preached among the Israelites, offered a perspective of being fair amid luxury for humans today. This study aims to present the theme of justice in luxury life. The writing of this article uses the synchronic method with the help of G. Lenski’s theory and analyses the world of the text and the world in front of the text, then adds the repertoire of searching expert opinions synthesized by the author. It’s acceptable to live a luxurious life if it doesn’t hurt others; that’s the message of the Prophet Amos, the messenger of God. Living in luxury is not wrong; it’s just not right when it is obtained from the sacrifices and suffering of others and even exhibited for the needy (Am 4:1-3, 5:11-12, 8:4-6). The Israelites forgot that the luxury they got was a gift from God. Abstrak: Dalam Kitab Amos gambaran hidup sosial itu begitu nyata. Sayangnya gambaran itu didominasi oleh situasi yang memprihatinkan yakni masyarakat mengalami penindasan oleh penguasa. Tetapi yang perlu dicermati ialah apakah mungkin keadilan sosial itu terjadi di masa itu? Jawabannya jelas mungkin sebagaimana diperjuangkan oleh para nabi, termasuk oleh Nabi Amos. Lalu, berlaku adil yang seperti apa yang dimaksud? Kisah Nabi Amos yang mewartakan di antara orang-orang Israel menawarkan kaca pandang berlaku adil di tengah kemewahan bagi manusia zaman ini. Penelitian ini hendak menyajikan tema keadilan dalam kemewahan. Penulisan artikel ini menggunakan metode sinkronis dengan bantuan teori G. Lenski dan menganalisa dunia di dalam teks dan di luar teks, kemudian menambah khasanah dari penelusuran pendapat para ahli yang disintesiskan oleh penulis. Hidup mewah boleh, asal tidak menyengsarakan sesama, seperti itu pesan Nabi Amos, sang utusan Allah. Hidup dalam kemewahan itu tidak salah, hanya saja tidak tepat di kala didapatkan dari pengorbanan dan penderitaan orang lain bahkan dipamerkan bagi yang berkekurangan (Am 4:1-3, 5:11-12, 8:4-6). Bangsa Israel lupa kalau kemewahan yang didapatkannya itu merupakan pemberian dari Allah.